2020
DOI: 10.1002/mds3.10060
|View full text |Cite
|
Sign up to set email alerts
|

Novel sensor to investigate microstructural contributions to corrosion of high‐palladium dental alloys

Abstract: There is incomplete understanding of corrosion mechanisms for high‐palladium dental alloys used for metal‐ceramic restorations. This investigation employed two complementary techniques as a novel sensor for an initial investigation of corrosion tendencies for phases in representative high‐Pd alloys with Pd–Cu–Ga and Pd–Ga compositions. After the initial oxidation step and simulated porcelain‐firing cycles, specimens were polished for examination by Scanning Kelvin Probe Force Microscopy and Atomic Force Micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Another study of high‐palladium alloys, 35 using a combined scanning Kelvin probe/atomic force microscopy technique, 36‐39 has shown that the ruthenium‐rich particles in the microstructures (arising from the use of ruthenium as a grain‐refining element), have higher Volta potential than the palladium solid solution matrix. These particles may thus act as locus points for the corrosion of the solid solution matrix with the release of Pd ions.…”
Section: Discussionmentioning
confidence: 99%
“…Another study of high‐palladium alloys, 35 using a combined scanning Kelvin probe/atomic force microscopy technique, 36‐39 has shown that the ruthenium‐rich particles in the microstructures (arising from the use of ruthenium as a grain‐refining element), have higher Volta potential than the palladium solid solution matrix. These particles may thus act as locus points for the corrosion of the solid solution matrix with the release of Pd ions.…”
Section: Discussionmentioning
confidence: 99%